Cash Waqf Based on CBDC in Countering the Financing of Radicalism and Terrorism in Indonesia - Muhammad M Said (Yayasan Inspirasi Merah Putih Indonesia, 2024)
This study aims to explore the role of the Central Bank Digital Currency (CBDC) within the framework of Islamic economics in preventing the financing of terrorism in Indonesia. The research highlights the misuse of religious concepts such as jihad by radical groups to justify acts of terrorism and how digital financial oversight can mitigate such activities. Through a qualitative approach, this research analyses data from governmental reports, and financial regulations on terrorism and terrorist financing, with a focus on how CBDC can increase financial transparency and reduce the risk of illicit transactions. The findings indicate that CBDC can significantly enhance the ability of central authorities to monitor suspicious financial activities, including the cross-border flow of funds used for terrorist purposes. By providing real-time transaction data, CBDC offers a robust tool for preventing the financing of terrorism. Additionally, the study emphasizes the importance of incorporating a correct and comprehensive understanding of jihad through educational programs as part of broader deradicalization efforts. This includes engaging religious leaders to counteract radical narratives that misuse Islamic principles. The research concludes that the implementation of CBDC can support the goals of maqasid al-shariah by promoting justice, protecting wealth, and safeguarding the welfare of society. As a policy recommendation, government should adopt CBDC to strengthen financial system, ensure transparency, and prevent the financing of terrorism, while also addressing the root causes of radicalization through education and financial inclusion programs.